Hamiltonian Cycle Problem in Strong k-Quasi-Transitive Digraphs With Large Diameter - Wang Ruixia (Discussiones Mathematicae Graph Theory, 2021)
Let k be an integer with k ≥ 2. A digraph is k-quasi-transitive, if for any path x0x1... xk of length k, x0 and xk are adjacent. Let D be a strong k-quasi-transitive digraph with even k ≥ 4 and diameter at least k +2. It has been shown that D has a Hamiltonian path. However, the Hamiltonian cycle problem in D is still open. In this paper, we shall show that D may contain no Hamiltonian cycle with k ≥ 6 and give the sufficient condition for D to be Hamiltonian.